ISOLATION AND IDENTIFICATION OF BURKHOLDERIA PSEUDOMALLEI FROM COWS ,GOAT’S MILK AND THEIR SURROUNDING ENVIRONMENT IN BASRAH PROVINCE - Adnan .M . AL-Rodhan Hanaa K. Ibrahim (Basrah Journal of Veterinary Research)
Two hundred samples (cow’s and goat’s milk75 for each,their farm soil 25and 25water samples )from different origin have been cultured on Ashdown selective agar which gave a higher percentage (36.5%)for B. pseudomallei isolation , 64% was observed in farm soil followed by water samples 48% than cow’s milk33.33% and finally the goat’s milk 26.66%. According to L-arabinose biotyping , 39.72% of the B.pseudomallei isolates were positive for arabinose (Arb+) and 60.3% of isolates were negative for arabinose (Arb-).The virulence testing revealed that most bacterial isolates yield haemolysin, protease, lipase and lecithenase in a percentage of 97.3% , 82.2%, 89.04% and 84.9% respectively.The Arb- biotypes were more virulent than Arb+ biotypes with significant differences (P< 0.05).All bacterial isolates were characterized by their ability to form capsule(100%),.This study confirmed the presence of casein proteolytic and necrotizing enzymes in the suspension of B.pseudomallei .Proteins concentration in this suspension was 0.00248 mg/ml .